1 HUBUNGAN PENGGUNAAN KONTRASEPSI SUNTIK DEPO MEDROKSI PROGESTERON ASETAT (DMPA) DENGAN PERUBAHAN FISIOLOGIS PADA WANITA USIA SUBUR (WUS) DI PUSKESMAS RANOMUUT KOTA MANADO - Kansil, Selfi Elisabeth; Kundre, Rina; Bataha, Yolanda (JURNAL KEPERAWATAN, 2015)
Abstract : Injectable contraceptive DMPA is an effective contraceptives that are injected into the body to prevent pregnancy and can cause changes such as weight gain, acne, dizziness and headache. The changes that occur not all be experienced by WUS because such changes are highly subjective complaints felt so different from one another. The purpose of this study was to determine correlation of contraceptive use DMPA injection with physiological changes in the health center WUS Ranomuut Manado. Methodology analysis survey with design cross sectional and statistical test by chi square test. The population in this study of WUS using the injected contraceptive DMPA who come to visit the health center Ranomuut Manado. This research using purposive sampling technique amounted 57 respondent. Results of statistical test p value = 0,028. This means that the value of p < Î± (0,05). The conclusion that there was correlation between the use of contraceptive DMPA injection with physiological changes in the health center WUS Ranomuut Manado. Suggestions for health workers in order to provide improved service to the DMPA injectable contraceptive use WUS and can explain the changes that will occur after WUS using DMPA injectable contraceptives.Keywords : Contraception DMPA injection, physiological changes, women of fertile age (WUS).